Appropriate technology and the labour share - Miguel A. León-Ledesma; Mathan Satchi (University of Kent, School of Economics, 2015)
We provide a general theoretical characterization of how technology choice affects the long-run elasticity of substitution between capital and labour. While the shape of the technology frontier determines the long-run growth path and the long-run elasticity, adjustment costs in technology choice allow capital-labour complementarity in the short run. We develop a class of production functions that are consistent with balanced growth even in the presence of permanent investment-specific or other kinds of biased technical progress but where, consistent with empirical evidence, short-run dynamics are characterized by complementarity. Importantly, the approach is easily implementable and yields a powerful way to introduce CES-type production functions in macroeconomic models. We provide an illustration within an estimated dynamic general equilibrium model and show that the use of the new production technology provides a good match for the short and medium run behavior of the US labour share.
Keywords: E25; O33; O40; 330; balanced growth; appropriate technology; elasticity of substitution